ETHNIC STUDENTS’ MOTIVATION AND LEARNING ENVIRONMENT IN ENGLISH LANGUAGE CLASSROOM IN BANGLADESH - Jiniya Bhoraty (Universitas Islam Sumatera Utara (UISU), 2026)
Despite increasing enrollment, ethnic students in Bangladesh face challenges in equitable language learning environments. This research examines obstacles and supportive factors influencing motivation to acquire English and provides insights for developing more inclusive and supportive educational practices for learning the English language. Self-determination theory (SDT) by Deci and Ryan has been applied to focus on three basic psychological needs of learners, such as autonomy, competence, and relatedness. Data was collected through interviews with 10 EFL teachers, classroom observations, and interviews with 30 students. The researcher followed the qualitative method to collect the data, and the data was analyzed using interpretive phenomenological analysis. Findings reveal cultural-linguistic, societal-institutional, and motivational factors affecting acquisition of ethnic students. Therefore, it is imperative to take approaches to cultural sensitivity, enhanced support systems, and policies that promote inclusivity and equal opportunities for all students. Teachers must recognize pronunciation challenges faced by ethnic students, which differ from Bengali learners.